Enucleation of a giant symptomatic gastric lipoma, a safe surgical approach. Issue 3 (27th March 2021) - Parreira, Rafaela; Rama, Tiago; Eloi, Teresa; Carneiro, Vítor; Leite, Maria Inês
Abstract: Gastric lipomas are rare, representing 2–3% of all benign tumours of the stomach. Most of these stomach neoplasms are small and detected incidentally during endoscopic or radiology evaluations. Computed tomography is highly specific imaging for lipoma diagnosis. Endoscopy and endoscopic ultrasound are other important diagnostic modalities to confirm the diagnosis. Identifying typical features can avoid biopsy or surgery in asymptomatic patients. In patients with larger lesions, usually more than 2 cm, clinical presentation may encompass haemorrhage, abdominal pain, pyloric obstruction and dyspepsia. As a result of its extreme low incidence, treatment is not standardized, though it is widely accepted that a symptomatic tumour mandates resection. Here, we present the case of a 60-year-old female presenting with abdominal pain and recurrent vomiting due to a giant gastric lipoma (80 × 35 × 35 mm). The patient underwent laparotomy and an enucleation was performed.